![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
Ta có :
\(x^3-3x^2+4=0\)
\(\Leftrightarrow\)\(x^3+x^2-4x^2-4x+4x=0\)
\(\Leftrightarrow\)\(\left(x-1\right)\left(x^2-4x+4\right)=0\)
\(\Leftrightarrow\)\(\left(x-1\right)\left(x-2\right)^2=0\)
\(\Leftrightarrow\orbr{\begin{cases}x-1=0\\x-2=0\end{cases}\Leftrightarrow\orbr{\begin{cases}x=1\\x=2\end{cases}}}\)
Vậy \(x=1\) hoặc \(x=2\)
\(x^3-3x^2+4=0\)
\(\Leftrightarrow\left(x^3+x^2\right)-\left(4x^2-4\right)=0\)
\(\Leftrightarrow x^2\left(x+1\right)-\left(4x-4\right)\left(x+1\right)=0\)
\(\Leftrightarrow\left(x+1\right)\left(x^2-4x+4\right)=0\)
\(\Leftrightarrow\left(x+1\right)\left(x-2\right)^2=0\)
\(\Leftrightarrow\orbr{\begin{cases}x+1=0\\x-2=0\end{cases}\Leftrightarrow}\orbr{\begin{cases}x=-1\\x=2\end{cases}}\)
Vậy...
![](https://rs.olm.vn/images/avt/0.png?1311)
a, \(x^3+x^2+4\)
\(=x^3+2x^2-x^2-2x+2x+4=0\)
\(=\left(x^3+2x^2\right)-\left(x^2+2x\right)+\left(2x+4\right)\)
\(=x^2\left(x+2\right)-x\left(x+2\right)+2\left(x+2\right)\)
\(=\left(x+2\right)\left(x^2-x+2\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(2x^2-x=3-6x\)
\(2x^2-x+6x-3=0\)
\(2x^2+5x-3=0\)
\(2x^2+6x-x-3\)
\(\left(2x-1\right)\left(x-3\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}2x-1=0\\x-3=0\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}x=\frac{1}{2}\\x=-3\end{cases}}\)
\(2x^2-x=3-6x\)
\(\Leftrightarrow2x^2+5x-3=0\)
\(\Leftrightarrow2x^2+6x-x-3=0\)
\(\Leftrightarrow2x\left(x+3\right)-\left(x+3\right)=0\)
\(\Leftrightarrow\left(2x-1\right)\left(x+3\right)=0\)
\(\Leftrightarrow2x-1=0\left(h\right)x+3=0\)
\(\Leftrightarrow x=\frac{1}{2}\left(h\right)x=-3\)
Vậy pt có tập nghiệm \(S=\left\{-3;\frac{1}{2}\right\}\)
TK HA!
![](https://rs.olm.vn/images/avt/0.png?1311)
a: 2x-(3-5x)=4(x+3)
=>2x-3+5x=4x+12
=>7x-3=4x+12
=>3x=15
=>x=5
b: =>x^2-4x+4=3(x-2)
=>(x-2)(x-5)=0
=>x=2 hoặc x=5
![](https://rs.olm.vn/images/avt/0.png?1311)
\(3x-6x-\dfrac{3}{4}=5x-\dfrac{7}{6}\)
\(\Leftrightarrow-3x-\dfrac{3}{4}=5x-\dfrac{7}{6}\)
\(\Leftrightarrow-3x-5x=-\dfrac{7}{6}+\dfrac{3}{4}\)
\(\Leftrightarrow-8x=-\dfrac{5}{12}\)
\(\Leftrightarrow x=-\dfrac{5}{12}:-8=\dfrac{5}{96}\)
\(4+\dfrac{x}{5}=\dfrac{5}{3}\\ \Rightarrow\dfrac{x}{5}=-\dfrac{7}{3}\\ \Rightarrow x=-\dfrac{35}{3}\)
\(4+\dfrac{x}{5}=\dfrac{5}{3}\)
=>\(\dfrac{x}{5}=\dfrac{5}{3}-4=-\dfrac{7}{3}\)
=>x=-7/3*5=-35/3